Asthma patients are at increased risk for adverse events and reoperation following posterior lumbar fusion - Julian Smith-Voudouris; Anshu Jonnalagadda; Arya G. Varthi; Jonathan N. Grauer (PLoS ONE, 2026)
Background Posterior lumbar fusion (PLF) is a common procedure for which patient factors are known to influence outcomes. Although asthma is comorbid for many PLF patients, it has not been assessed for correlation to adverse events following PLF. We used a national administrative database to evaluate the relative odds of adverse events following PLF in patients with versus without asthma. Methods Adult patients undergoing primary one- or two-level PLF with or without interbody fusion were identified from 2015 – 2023Q1 PearlDiver datasets. Asthma patients were matched 1:4 based on age, sex, and Elixhauser Comorbidity Index (ECI). The incidence of 90-day adverse events were compared using multivariable logistic regression. Five-year reoperations were compared with Cox proportional hazards modeling. The matched asthma group was then stratified by disease severity for multivariable analysis of 90-day aggregated adverse events. Results After matching, 19,078 asthma patients undergoing PLF were compared to 75,838 patients without asthma. Asthma patients were at increased odds of 90-day pulmonary adverse events, (p < 0.0001 for each) as well as non-pulmonary adverse events (p < 0.0001 for each). These associations increased in odds with increasing severity of asthma. Further, asthma patients had significantly higher rates of five-year revision, reflected by lower reoperation free survival compared with non-asthma patients (89.2% versus 92.6%, p < 0.0001). Conclusions Over a tenth of patients undergoing PLF were identified as having asthma and were found to be of greater odds of pulmonary and non-pulmonary adverse events (a trend that increased with asthma severity), as well as five-year revisions. Stringent pre-operative optimization and postoperative management strategies should be employed for asthma patients undergoing PLF.